High-Availability Databases in Global Banking : Ensuring Continuous Operations and Data Integrity - Uday Kumar Manne (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
This comprehensive article explores the critical role of high-availability (HA) database systems in global banking operations, focusing on their impact on continuous service delivery, data integrity, and regulatory compliance. The article examines the challenges faced by financial institutions in maintaining reliable database systems, including the risks of downtime, data inconsistencies, and the complexities of managing distributed systems across multiple jurisdictions. It provides an in-depth analysis of various HA database architectures, comparing active-active and active-passive configurations, and discussing replication mechanisms and clustering strategies. Through case studies of real-world implementations in trading and core banking systems, the research highlights best practices and common challenges in deploying HA solutions. The article also investigates the broader implications of HA databases on operational resilience and regulatory adherence, particularly in the context of SOX and Basel III requirements. Looking ahead, the article explores emerging trends in HA database technology, including cloud-based solutions, the potential of blockchain for enhancing data integrity, and the role of artificial intelligence in improving system reliability. By synthesizing technical insights with practical applications, this research offers valuable guidance for financial institutions seeking to enhance their database infrastructure to meet the demands of an increasingly digital and interconnected global financial system.